Analisis Keamanan Informasi dalam Sistem Informasi Manajemen: Tantangan dan Solusi di Era Cybersecurity - Abdul Azis Nasution; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
Information security has become a major concern for organizations in today's digital era. In the context of management information systems (MIS), information security challenges are increasingly complex with increasing cyber threats. This research aims to analyze the main challenges in maintaining information security in MIS and present effective solutions in facing the cybersecurity era. Through a literature and case study approach, we identify common vulnerabilities, attack methods used by attackers, and solutions and best practices that organizations can implement to improve information security in MIS. The results of this research provide valuable insights for practitioners and decision makers in managing information security risks in an ever-changing business environment.